Direct Oral Anticoagulant Use: A Practical Guide to Common Clinical Challenges - Ashley Chen; Eric Stecker; Bruce A. Warden (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2020)
Abstract Direct oral anticoagulants (DOACs) have quickly become attractive alternatives to the long‐standing standard of care in anticoagulation, vitamin K antagonist. DOACs are indicated for prevention and treatment of several cardiovascular conditions. Since the first approval in 2010, DOACs have emerged as leading therapeutic alternatives that provide both clinicians and patients with more effective, safe, and convenient treatment options in thromboembolic settings. With the expanding role of DOACs, clinicians are faced with increasingly complex decisions relating to appropriate agent, duration of treatment, and use in special populations. This review will provide an overview of DOACs and act as a practical reference for clinicians to optimize DOAC use among common challenging scenarios. Topics addressed include (1) appropriate indications; (2) use in patients with specific comorbidities; (3) monitoring parameters; (4) transitioning between anticoagulant regimens; (5) major drug interactions; and (6) cost considerations.